Harga diri sebagai mediator pengaruh pola asuh otoritatif terhadap resiliensi remaja - Siti Rezeki Emelia; Diah Karmiyati; Cahyaning Suryaningrum (Universitas Muhammadiyah Malang, 2021)
Adolescence is marked by many changes so that adolescents will face difﬁcult and challenging situations. The ability to adapt to difﬁcult situations affects the development and psychological well-being of adolescents. Resilience is an individual’s ability to adapt to adversity and challenges. This study aims to examine the role of self-esteem in mediating the effect of authoritative parenting on resilience. The sampling technique in this study used accidental sampling using a web survey Google Form. Participants were 160 teenagers, aged 12 to 18 years. The instruments used were the Parenting Style Scale Index (PSI), Resilience Scale 14 (RS-14) and the Rosenberg Self-Esteem Scale (RSES). The results showed that self-esteem mediates the effect of authoritative parenting on adolescent resilience.